Psychological and biographical determinants of entrepreneurial intention: Does the learning environment act as a mediator? - Mateo M. Córcoles-Mu\~noz; Gloria Parra-Requena; María José Ruiz-Ortega; Pedro M. García-Villaverde; Francisco J. Ramírez-Fernández (Administrative Sciences, 2019)
The aim of this research is to study the mediating role of the learning process in explaining the relationships between certain psychological and biographical characteristics and entrepreneurial intention. The findings suggest that the effect of psychological and biographical aspects on entrepreneurial intention depend on the extent to which students are able to take advantage of their personal capabilities in order to develop an effective learning process. Learning process factors (information about course guides, student effort and educational processes) mediate the relationships between specific psychological factors (achievement need, internal control and autonomy) and entrepreneurial intention. With regard to biographical factors, we find no mediating effect on entrepreneurial intention through the learning process. The present study provides a better understanding of the antecedents of entrepreneurial intention, helping to fill the gap in the literature.
Keywords: 350; entrepreneurial intention; learning process; entrepreneurial education; psychological factors; biographical factors; mediating model